Information, Attention, and Decision Making - van Knippenberg, Daan; Dahlander, Linus; Haas, Martine R.; George, Gerard (Academy of Management Journal, 2015)
An introduction is presented in which the editor discusses various reports within the issue on topics including the competitive use of information, biases in information-processing and decision-making, and the role of rational calculus and retributive justice in sanctioning of norm violations..